Multiattribute analysis of a pleistocene fluvial system using RGB color blending and self-organizing maps - Babikir, I. (Society of Exploration Geophysicists, 2020)
A multiattribute analysis has been carried out on near-surface Pleistocene strata where the seismic data quality is very good. Relevant seismic attributes that have a proven application in the fluvial system were generated and analyzed. RGB color blend along with self-organizing maps were applied to reveal the depositional architecture of the interval. The extracted time slices were effectively characterized the depositional elements of the fluvial system. Â© 2020 Society of Exploration Geophysicists.